Detection of potentially toxic cyanobacteria in colombian lakes using toxicity bioassays and PCR based on the Microcystin Synthetase Subunits A (mcyA) & E (mcyE) and nodularin synthetase subunit F (ndaF) genes (2016)
Ingeniero Ambiental